2012
DOI: 10.1093/nar/gks232
|View full text |Cite
|
Sign up to set email alerts
|

Real-time assay for testing components of protein synthesis

Abstract: We present a flexible, real-time-coupled transcription–translation assay that involves the continuous monitoring of fluorescent Emerald GFP formation. Along with numerical simulation of a reaction kinetics model, the assay permits quantitative estimation of the effects on full-length protein synthesis of various additions, subtractions or substitutions to the protein synthesis machinery. Since the assay uses continuous fluorescence monitoring, it is much simpler and more rapid than other assays of protein synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 52 publications
1
40
0
2
Order By: Relevance
“…The SNAP reaction has been measured at rates that compare favorably with the maturation rate of EmGFP (see Supplemental Information; Iizuka et al 2011), a previously reported effective signal of productive translation (Rosenblum et al 2012). Also, the SecM minimal arrest sequence almost ensures that the SNAP f reaction occurs prior to the completion of termination.…”
Section: Quantification Of Wild-type Ribosome Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The SNAP reaction has been measured at rates that compare favorably with the maturation rate of EmGFP (see Supplemental Information; Iizuka et al 2011), a previously reported effective signal of productive translation (Rosenblum et al 2012). Also, the SecM minimal arrest sequence almost ensures that the SNAP f reaction occurs prior to the completion of termination.…”
Section: Quantification Of Wild-type Ribosome Activitymentioning
confidence: 99%
“…The throughput and generality of these methods are limited by the requirement for multiple steps of processing or specialized equipment to obtain a translation signal. An elegant high-throughput method has been reported in which synthesis of fast-maturing Emerald GFP (EmGFP) produces a detectable fluorescent signal upon translation (Rosenblum et al 2012). However, this method is limited by the requirement of oxygen for maturation of GFP, which interferes with fluorescence detection at the single-molecule level.…”
Section: Introductionmentioning
confidence: 99%
“…We next assessed the mechanism of action of azide 2 and anti -triazoles 1 , 19–32 and evaluated their antibiotic activities using (1) in vitro protein synthesis assays using a cell-free system 50 and (2) minimum inhibitory concentration (MIC) assays for azide 2 , anti- triazoles 1 , and 19–32 (Table 3). 51 As the ribosome-templated in situ click process delivers bivalent inhibitors possessing greater potency than their monovalent components, it is important to determine the selectivity of the newly formed cycloadducts for bacterial versus mammalian ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The assays also allow for detection of undesired off-target effects for compounds not anticipated to interfere with proteostasis. Furthermore, in vitro systems are available for detecting inhibition of transcription and translation (using the minimum required biological components), 2, 22 or direct inhibition of the proteasome, but the cellular environment is an intrinsically more complex environment, and multiple biological factors play a role in proteostasis. The combination of these new in-cell assays with existing in vitro assays may allow for validation or exclusion of specific targets in the complex machinery regulating protein levels.…”
Section: Discussionmentioning
confidence: 99%